Visa gramaticalizar : o processo de gramaticalização de visar - Moura, Geovana Portela de (2016)
This paperwork, developed within the Project for the History of the Brazilian Portuguese - Mato Grosso (PHPB-MT), aims to study the linguistic change process of the constructions with the verb aim (visar in Brazilian Portuguese). Therefore, it is based on studies of Grammaticalization (GR) from the perspective of Functional Linguistics, according Bybee (2010), Hopper (1991), Hopper & Taugott (1993), Heine & Traugott (1991), Gonçalves et al. (2007) and Lopes-Damasio (2008, 2011). The GR, while theory and process, will be understood as a productive reinterpretation mechanism of available linguistic material in the language repertory. In this perspective, focuses items in more grammatical constructions that arise from the extent of the use of lexical items, as well as less grammatical items, in a process of change directly linked to the communicative act. This study is divided into two distinct periods, but intrinsically associated: (i) of bibliographic nature, in which intends to make a grounding to GR, starting on the theoretical approach of its conception to its fundamental mechanisms; (II) of empiric nature, in which it was map the GR trajectory of the constructions with the verb Visar, through an analytical-description of the syntactic, semantic and pragmatic behavior of the item according to the assumptions of GR. Occurrences with this research’s object was be raised and analyzed from a panchronic sample; in other words, the combination between the synchronic and diachronic samples, extracted from written and published papers in Mato Grosso state in XIX, XX and XXI centuries; in order to capture the change and testify the historical change of the phenomenon under study. We concluded that visar is a GR process, wherein he part of the more concrete use as a complete verb, meaning to look at a more abstract use in the formation of periphrasis (visar + infinitive) with volition marking.